(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Non-alcoholic fatty liver disease (NAFLD) is increasingly common worldwide, with a substantial proportion progressing to non-alcoholic steatohepatitis (NASH) and fibrosis. In India, metabolic risk factors are rising, and biopsy studies suggest that over 60% of NAFLD patients have NASH, with 30–35% showing advanced fibrosis. Histologic diagnosis of NASH (macrovesicular steatosis, ballooning degeneration, and inflammation) is the gold standard. We examined liver biopsy samples from Indian adults with NAFLD to characterize histopathological patterns and correlate these with clinical features. Materials and Methods: We conducted a retrospective analysis of 150 adult patients with biopsy-proven NAFLD (exclusion of other etiologies) at a tertiary center in India. Liver biopsies were scored by standard criteria (Brunt et al.) for steatosis grade (1–3), lobular inflammation (0–3), hepatocyte ballooning (0–2), portal inflammation (0–3), and fibrosis stage (0–4). NASH diagnosis required steatosis ≥5%, ballooning, and lobular inflammation. Clinical data (age, gender, BMI, diabetes, hypertension, metabolic syndrome, liver enzymes) were recorded. Continuous variables were compared by t-test or Mann–Whitney U test and categorical by chi-square. Logistic regression identified factors independently associated with NASH. Statistical significance was set at p<0.05. Results: Among the 150 NAFLD patients (mean age 47±12 years, 60% male), 45 (30%) had definite NASH, 50 (33%) had borderline NASH, and 55 (37%) had simple steatosis (no NASH). NASH patients were older (52.1±11.3 vs 44.5±12.1 years, p=0.004), had higher BMI (28.5±4.3 vs 24.8±3.5 kg/m², p<0.001), and greater prevalence of type 2 diabetes (44% vs 17%, p=0.001), hypertension (33% vs 15%, p=0.02) and metabolic syndrome (67% vs 33%, p<0.001) than non-NASH patients (Table 1). ALT and AST levels were significantly higher in NASH (mean ALT 80 vs 45 U/L, AST 70 vs 40 U/L; p<0.001 for both). On histology (Table 2), moderate-to-severe steatosis (grade 2–3) was seen in 75% of NASH cases; ballooning (score ≥1) was present in 89% and lobular inflammation (score≥1) in 89%. Mallory–Denk bodies were noted in 12 (26.7%) of NASH biopsies. Fibrosis was present in 30 (66.7%) of NASH patients: stage 0 (none) in 15 (33.3%), stage 1 in 10 (22.2%), stage 2 in 7 (15.6%), stage 3 in 6 (13.3%), and stage 4 (cirrhosis) in 7 (15.6%). Thus advanced fibrosis (stage ≥3) occurred in 24.4% of NASH patients, similar to the 30% reported in Indian series. Figure 1–3 show representative histology. In multivariate analysis (Table 3), BMI >25 kg/m² (OR 4.2; 95% CI 2.2–8.1; p<0.001), diabetes (OR 3.5; 95% CI 1.8–6.8; p<0.001), and age >50 years (OR 2.1; 95% CI 1.2–3.6; p=0.01) were independently associated with NASH. Female gender and mild ALT elevation were not significant predictors. Conclusion: In this Indian cohort, NASH was present in about one-third of biopsy-proven NAFLD patients. NASH was strongly associated with obesity, diabetes, and metabolic syndrome, underscoring metabolic dysfunction as a driver of disease. Histologically, most NASH biopsies showed moderate-to-severe steatosis, ballooning degeneration, and varying degrees of fibrosis, with nearly one-quarter having advanced fibrosis (stage 3–4). These findings align with reports that Indian NAFLD often presents with aggressive histology. Early recognition of at-risk patients (e.g. older, obese, diabetic individuals) is crucial, as NASH carries a high risk of progression to cirrhosis and hepatocellular carcinoma.